Typological Usage of the Old Testament in the New Testament - Piotr Ł abuda (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2011)
The typological reading and application of Hebrew texts deserve the greatest attention among the numerous ways of reading and applying the Old Covenant ideas, traditions and texts. Through the typological reading and application of the text, the text is given broad latitude for its typological application. Treating the Bible from the typological point of view is not only restricted to quoting the books of the Old Testament. Instead, numerous allusions and references to events, characters, places and descriptions are made. The interpretation of these analogies leads to the understanding of the whole truth of the Old and New Testament. “Christians therefore read the Old Testament in the light of Christ who died and rose from the dead. Such typological reading reveals an inexhaustible part of the Old Testament” (CCC 129). Therefore typological thinking is necessary in order to interpret the Bible messages appropriately.